I'm trying to find the obliques asymptotes of the following function: $$f(x)=|x-1| \log\Big(\sqrt{x^2 +3x+3}-x-1\Big)$$

Its domain should be this: $D(f)=(-\infty, +\infty)$;

I discussed the absolute values: $$|x-1|=\left\{ \begin{array}{c} x-1 <=>x\geq1 \\ 1-x <=>x\lt 1 \end{array} \right. \ \text{and}\ \ |x|=\left\{ \begin{array}{c} x <=>x\geq0 \\ -x <=>x\lt0 \end{array} \right.; $$

When $f(x)$ approaches to the left border: $$\lim_{x\to\ - \ \infty} (1-x) \log\Bigg((-x)\sqrt{1 +\frac3x+\frac3{x^2}}-x-1\Bigg)=+\infty \ ;$$

When it goes to the right border: $$\lim_{x\to\ + \ \infty} (x-1) \log\Big(\sqrt{x^2 +3x+3}-x-1\Big)=-\infty \ ;$$

Now I want to find obliques asymptotes. $$m = \lim_{x\to\ - \ \infty} \frac{f(x)}{x}=\lim_{x\to\ - \ \infty}\frac1x(1-x) \log\Bigg((-x)\sqrt{1 +\frac3x+\frac3{x^2}}-x-1\Bigg)= - \infty \ ;$$ For $x\to-\infty$ I do not have oblique asymptote. So, I check for the right border: $$m = \lim_{x\to\ + \ \infty} \frac{f(x)}{x}=\lim_{x\to\ + \ \infty}\frac1x(x-1) \log\Bigg((x)\sqrt{1 +\frac3x+\frac3{x^2}}-x-1\Bigg)= \frac1x x \Bigg(1-\frac1x\Bigg) \log\Bigg(\frac12\Bigg)= \log\Bigg(\frac12\Bigg) \ ;$$

Here comes my problem, I'm not able to find $q$, the "known term". $$q = \lim_{x\to\ + \ \infty} f(x) - mx=\lim_{x\to\ + \ \infty}(x-1) \log\Bigg((x)\sqrt{1 +\frac3x+\frac3{x^2}}-x-1\Bigg) -\log\Bigg(\frac12\Bigg)x = + \infty\cdot 0 \ ;$$ But this is undetermined form and I'm not able to solve it.

Could someone point me out where I'm doing wrong or just give me a hint to find the correct solution? Thank you.


We have \begin{align} \log\bigl(\sqrt{x^2 +3\,x+3}-x-1\bigr)-\log\Bigl(\frac{1}{2}\Bigr)&= \log\Bigl(\frac{x+2}{\sqrt{x^2 +3\,x+3}+x+1}\Bigr)-\log\Bigl(\frac{1}{2}\Bigr)\\ &=\log\Bigl(\frac{2\,x+4}{\sqrt{x^2 +3\,x+3}+x+1}\Bigr)\\ &=\log\Bigl(1+\frac{x+3-\sqrt{x^2 +3\,x+3}}{\sqrt{x^2 +3\,x+3}+x+1}\Bigr)\\ &=\log\Bigl(1+\frac{3\,x+6}{\bigl(\sqrt{x^2 +3\,x+3}+x+1\bigr)\bigl(\sqrt{x^2 +3\,x+3}+x+3\bigr)}\Bigr)\\ &\sim\frac{3}{4\,x}\quad\text{as}\quad x\to+\infty. \end{align} Then \begin{align} f(x)-\log\Bigl(\frac{1}{2}\Bigr)\,x&= x\Bigl(\log\bigl(\sqrt{x^2 +3\,x+3}-x-1\bigr)-\log\Bigl(\frac{1}{2}\Bigr)\Bigr)-\log\bigl(\sqrt{x^2 +3\,x+3}-x-1\bigr)\\&\sim\frac34+\log2. \end{align}

  • $\begingroup$ Really thank you! The result should be $\frac34 + \log(2)$. I think you have forgot to solve $\log\Big(\sqrt{x^2 +3x+3}-x-1\Big)$ but it should be fine. $\endgroup$ – NapMaster Jun 3 '18 at 11:31
  • $\begingroup$ I have edited my answer . Thanks for commenting. $\endgroup$ – Julián Aguirre Jun 3 '18 at 11:39

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.